A qualitative study on the use of mobile-based intervention for perinatal depression among perinatal mothers in rural Bihar, India. (August 2021) - Seshu, Uttara; Khan, Homam A; Bhardwaj, Manish; Sangeetha, C; Aarthi, G; John, Sujit; Thara, R; Raghavan, Vijaya
Background: Perinatal depression (PND) is one of the most common psychiatric illnesses in women, with a prevalence around 22% in India. Leveraging mobile-based technologies could help in the prevention and treatment of perinatal depression even in remote places. Understanding the experiences and barriers of using such technology interventions by perinatal mothers could help in the better design and in delivery of these interventions. We aimed to study the experiences of the perinatal women using a mobile phone-based intervention, Interactive Voice Response System (IVRS), for the prevention and management of perinatal depression in a rural district of Bihar, India. Materials and methods: A total of 12 in-depth interviews (IDIs) and one focus group discussion (FGD) with eight participants were conducted with perinatal mothers using the mobile-based IVRS to explore the experiences and perspectives of women receiving mobile phone-based interventions for the treatment of PND. Thematic analysis was done to identify major themes. Results: Five major themes emerged from the study around accessibility, usability, community participation, cost and preference to either intervention. Women found the mobile-based intervention useful as it made them feel lighter. They considered mental health as a health issue and wanted help to address their problems. They became familiar with terms like anxiety, depression, helplessness and burden and bean using them in their conversations. The patients used therapeutic strategies such as breathing, coping and relaxation. They even agreed to take up sessions for their peer group. Conclusion: Women in rural Bihar seemed satisfied with the technology-based intervention. It has made mental health issues more visible and acceptable even in the rural hinterlands of Bihar.